German Mission in Abyssinia: Wilhelm Staiger from Baden, 1835–1904 - Perry, Yaron (Aethiopica, 2008)
This article deals with the story of the Christian mission among the Jews of Ethiopia during the 1860s as related in the memoirs of the German missionary, Wilhelm Staiger, publicised here for the first time. Staiger who had, together with scores of other European missionaries, become caught up in the political turmoil between Great Britain and Teodoros, King of Ethiopia, describes the affair in the first person.